PENERAPAN PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIOLOGI HEWAN BERBASIS INKUIRI SEBAGAI UPAYA MEMBENTUK HABITS OF MIND MAHASISWA - Masiah Masiah; Ali Imran (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2017)
Abstract: The tendency to think is important to be shaped and honed, as a preparation to prepare students to be a competing person in all fields. This can be done by providing a challenging experience in learning so that from these experiences can spur his brain to always think. The purpose of this research is to apply the development of valid and effective inquiry of animal physiology-based learning device so that it can form student's habits of mind. The results showed N-Gain test result 0.73 with high category and habits of mind of students who assessed through questionnaire have average score 74,5 with good category. The observation of student's habits of mind shows improvement from the first meeting to the last meeting. The results show that the application of development of specific inquiry-based animal physiology learning tools leads to the formation of student's habits of mind, valid empirically and positively affect student learning outcomes.